How To Improve Analytical Writing Skills in ESP Learning - Khmyzova, Olha Vasylivna (Одеський національний економічний університет, 2025)
Improving analytical writing skills in English for Specific Purposes (ESP) learning is crucial for achieving both academic and professional success. In this paper, the definition of analytical writing is discussed, as well as its importance and how analytical writing skills can be developed in ESP learning. Analytical writing can be defined as a type of writing that requires the analysis of data, facts, a text or a situation, and the subsequent formation of arguments based on the findings. Students often find analytical writing in English challenging, but it is considered a valuable professional skill that can be developed through practice. A key challenge for teachers is the heterogeneity of students’ needs, which necessitates the provision of tailor-made writing instruction that addresses specific genres and discourse communities. Another noteworthy challenge pertains to the balancing act of imparting writing skills with domain-specific language. To address the challenges previously mentioned, several strategies can be applied: 1) adoption of a genre-based approach; 2) collaboration between language instructors and subject specialists; 3) incorporation of technology and multimedia resources.

Вдосконалення навичок аналітичного письма у вивченні англійської мови за професійним спрямуванням має вирішальне значення для досягнення як академічного, так і професійного успіху. У даній доповіді буде розглянуто визначення аналітичного письма і стратегії розвитку його навичок під час вивчення англійської мови за професійним спрямуванням. Аналітичне письмо – вид письма, що потребує аналізу даних, фактів, тексту або ситуації, а також подальшого формування аргументів на основі отриманих результатів. Студенти часто відчувають труднощі з аналітичним письмом англійською мовою, але воно є цінною професійною навичкою, яку можна розвинути практичним шляхом. Ключовим проблемним моментом для викладачів є гетерогенність потреб студентів, що зумовлює необхідність надання індивідуальних інструкцій з письма, орієнтованих на конкретні жанри та дискурсивні спільноти. Інший важливий чинник пов’язаний з балансуванням між розвитком навичок письма та використанням мови певної галузі. Для вирішення вищезгаданих труднощів можна застосувати кілька стратегій: 1) жанровий підхід; 2) організація співпраці між викладачами іноземних мов та інших навчальних дисциплін; 3) використання цифрових технологій і мультимедійних ресурсів.
Keywords: English for Specific Purposes (ESP); analytical writing skills; higher legal education; training of lawyers; ESP learning; Англійська мова за професійним спрямуванням; навички аналітичного письма; вища правнича освіта; підготовка правників; вивчення англійської мови за професійним спрямуванням